Blood oath [large type] - Lenhardt, Melissa (Lenhardt, Melissa. Sawbones series, 2017)
"Outlander meets post-Civil War unrest in this nonstop sequel to Sawbones ... Laura Elliston and William Kindle are on the run -- from the Army and from every miscreant in the West eager to claim the $500 bounty for Laura's capture as their own. But the danger isn't just from those pursuing them. Laura and Kindle have demons of their own and a past that won't stay dead. Exhausted, scared, scarred and surrounded by enemies, neither realize the greatest danger is yet to come"-- Provided by publisher.